Upper extremity evaluation test through TEMPA: Reference values, age, gender, dominance effect and relation to dexterity - S.M. Michaelsen; A.C. Ovando; M.A. Natalio; G.Z. Mazo; L.C. Rodrigues (Desafio Singular, 2011)
The purpose of this study was to verify the effect of age, gender and dominance on upper limb functional capacity and develop reference values on Functional performance test for upper extremity, Brazilian version of TEMPA (Test d'Evaluation de la performance des Membres supérieurs dês Personnes Agées), and verify the relationship between hand and digital dexterity and arm functional capacity. Participated in the study 281 individuals, aging more than 40 years old. Manual dexterity and finger dexterity were assessed with Box and Blocks Test (BBT) and Nine Hole Peg Test, respectively. ANOVA evaluated the effects of age in men and women and effects of gender and laterality. Pearson`s correlation evaluated the relation between dexterity and upper limb function. In 70 to 79 years strata and the strata older than 80 TEMPA tasks have shown a decline compared to the younger strata. No significant differences were see between 40-49, 50-59 e 60-69 years old strata for any task. Decline in digital dexterity in women and in hand dexterity in man was correlated with decrease in upper limb function. The knowledge on effects of aging on upper limb function and dexterity will help differentiate between normal and pathological aging in upper extremity performance.